Yet another dark side of chivalry: Benevolent sexism undermines and hostile sexism motivates collective action for social change - Becker, Julia C; Wright, Stephen C (Journal of personality and social psychology, 2011)
The current research tests a model for understanding how benevolent sexism undermines, whereas hostile sexism promotes, social change. Study 1 (N = 99) and Study 2 (N = 92) demonstrate that exposing women to benevolent sexism decreases their engagement in collective action, whereas exposure to hostile sexism increases it. Both effects were mediated by gender-specific system justification and perceived advantages of being a woman. In Study 2, positive and negative affect also mediated these relationships. Results from Studies 3 and 4 (N = 68 and N = 37) support the causal chain described in the mediational models tested in Studies 1 and 2. Manipulations that increased gender-specific system justification (Study 3) and perceived advantages of being a woman (Study 4) reduced intentions to participate in collective action.